The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1007/s00401-004-0845-z
|View full text |Cite
|
Sign up to set email alerts
|

Blood-brain barrier is impaired in the hippocampus of young adult spontaneously hypertensive rats

Abstract: A causative role of blood-brain barrier (BBB) impairment is suggested in the pathogenesis of vascular dementia with leakage of serum components from small vessels leading to neuronal and glial damage. We examined the BBB function of young adult spontaneously hypertensive rats (SHR) in order to determine earlier changes in the BBB in chronic hypertension. SHR and stroke-prone SHR (SHRSP) were injected with horseradish peroxidase (HRP) as an indicator of BBB function and compared with Wistar Kyoto rats (WKY). Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
79
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 90 publications
(85 citation statements)
references
References 41 publications
5
79
0
1
Order By: Relevance
“…However, a growing body of evidence addresses alterations in BBB permeability (typically to large molecules). For example, increases in BBB permeability have been reported to accompany aging (Shah and Mooradian, 1997), Alzheimers dementia (Skoog et al, 1998;Ujiie et al, 2003), type II diabetes (Starr et al, 2003), and hypertension (Mooradian, 1988;Mayhan, 1990;Ueno et al, 2004). BBB permeability also increases with increasing plasma osmolarity (Tamaki et al, 1984), and after the administration of certain drugs (Boertje et al, 1992).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…However, a growing body of evidence addresses alterations in BBB permeability (typically to large molecules). For example, increases in BBB permeability have been reported to accompany aging (Shah and Mooradian, 1997), Alzheimers dementia (Skoog et al, 1998;Ujiie et al, 2003), type II diabetes (Starr et al, 2003), and hypertension (Mooradian, 1988;Mayhan, 1990;Ueno et al, 2004). BBB permeability also increases with increasing plasma osmolarity (Tamaki et al, 1984), and after the administration of certain drugs (Boertje et al, 1992).…”
Section: Central Nervous Systemmentioning
confidence: 99%
“…Effects of genetic factors cannot be disregarded. The earlier study 4 also showed that collagen deposits were occasionally seen in the BBB-damaged vessels. In addition, Iwanaga et al 16 microdissected vascular samples from the hippocampus of SHRSP and WKY rats and examined the difference in gene expression between the vascular samples with BBB impairment of SHRSP and those without impairment of WKY, using a microarray assay.…”
Section: Discussionmentioning
confidence: 78%
“…The earlier study 4 showed that the BBB function was deteriorated in vessels located along hippocampal fissures of 3-month-old SHRSP, but not in same-age WKY rats. The present study indicated that the gene and protein expression of MMP-13 were increased in hippocampal samples in SHRSP compared with those in WKY rats and that MMP-13 was present in the cytoplasm of perivascular cells of microglia/ macrophage lineage.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…8,9 Moreover, blood-brain barrier alters with aging and even in some normal brain structures such as the olfactory bulb, hippocampus and periventricular areas, [10][11][12] and bloodbrain barrier dysfunctions with the development of capillary collagenosis have been revealed not only in Binswanger disease brains, 13,14 but also spontaneously hypertensive rats and a rat model of chronic cerebral hypoperfusion. 15,16 Recently, it has been shown that the intra-cranial capillary diameter is regulated by pericyte contraction under noradrenergic and purinergic neurotransmitter influences. 17 All the above findings suggest that a failure in autonomic control of cerebral circulation and damage in blood-brain barrier under untreated hypertension have significant roles in the pathogenesis of MCI/vascular cognitive impairment.…”
mentioning
confidence: 99%